The Influence of Taxpayers, Tax Services and Taxpayer Compliance on Tax Revenues at the Cimahi Pratama Tax Service Office - Uswatun Hasanah; Ari Bramasto; Trisna Sutrisna (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
This research aims to find out the influence of Taxpayer Awareness, Tax Services and Taxpayer Compliance To Tax Revenues at the Office of Tax Services Pratama Cimahi. The methods used in this study are descriptive methods and verifiative methods. The type of data used in this study is the type of primary data where this data is taken directly from respondents with research using questionnaires shared with respondents that contain questions that must be filled out by respondents by applying the Yamane formula of 100 respondents to taxpayers registered with KPP Pratama Cimahi. The statistical tests used in this study are Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroskedasticity Test, Multiple Linear Regression Test, Determination Coefesien Test (R2), Hypothesis Test, with statistical data processing using SPSS 28.0 program. The results showed that taxpayer awareness, taxpayer services and taxpayer compliance had a partial effect on tax revenues that can be seen from the results of the t test where thitung>ttabel with each value is awareness of taxpayers (4,239>1,985), tax services (3,259>1,985), and taxpayer compliance (4,226>1,985). Taxpayer awareness, tax services and tax compliance have a simultaneous and significant effect on tax revenues that can be seen from the results of the f test where fhitung>ftabel is 80,548>2.70.